Maisie morris and the whopping lies - Nadin, Joanna; Robins, Arthur (Walker London, 2005)
Maisie Morris lives with her mum and her pet monkey in the small town of Groutley where nothing exciting ever happens. So when the local newspaper reports mysterious goings-on, Maisie decides to investigate